Evaluation of pre-operative clinical finding and per-operative assessment of carcinoma stomach in tertiary settings of Bangladesh - Nahar, Mst Jesmen; Matubber, Md Mahiuddin; Rahman, Md Mahbubur; Rahman, Md Mahbubur; Billah, Syed Muhammad Baqul; Sayed, MMA; Siddique, Md Ibrahim; Alam, AHM Towhidul (Journal of Surgical Sciences, 2020)
Background: Carcinoma stomach, a major killer cancer all over the world, is still presenting late in developing countries due to delay in early diagnosis, lack of awareness, infrastructure etc. Objectives: To establish the importance of preoperative evaluation on operability of carcinoma stomach. Methods: Sixty clinically and histopathologically diagnosed ca stomach cases who underwent surgery in department of Bangabandhu Sheikh Mujib Medical University, Dhaka, and Dhaka Medical College Hospital, Dhaka in 2011 were assessed with clinical picture, investigations, preoperative evaluation and peroperative findings were recorded. Z test for proportion was used to assess clinical decision predictability with a p value of :s;0.05 as significant. Results: Male (73.33%) predominant with 2.75:1 male:female ratio was observed. Mobility, fixity and abdominal lymphadenopathy were not well detected through clinical assessment (p=0.001) while ascites, metastasis and Shelf of Slummer were similar in both clinical and operative finding. The endoscopy of upper GIT finding gave a unique picture as the findings were almost same as were found during operation. USG detected a lesser proportion of the clinical condition compared to peroperative condition whereas CT performed better than the USG except for the lesion detection. Though Computed Tomography (CT) detected higher percentage of lesion, metastasis, ascites and lymph node involvement compared to ultrasonogram (USG), it was significantly higher only for lesion detection (p=0.002) and lymph node involvement (p=<0.001). In the similar manner USG assessment of lesion detection (p=<0.001) and lymph node involvement (p=0.003) was significantly low compared to operative finding. When we looked between CT and operative finding only lesion detection was significantly low (p=0.01) indicating CT to be most effective predictor of clinical picture for operative decision. Preoperative plan were mostly not in accordance with peroperative decision except for total gastrectomy. Conclusion: The study indicates weakness in clinical detection and pre-operative plan compared to per-operative finding. Hence combination of clinical feature and investigation tools especially endoscopy of upper GIT combined with CT is recommended to predict a better operative decision. Journal of Surgical Sciences (2018) Vol. 22 (1): 43-46